2020
DOI: 10.1016/j.antiviral.2019.104661
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling deISGylating and deubiquitinating activities of the MERS virus papain-like protease

Abstract: A B S T R A C TCoronavirus papain-like proteases (PLPs or PLpro), such as the one encoded in the genome of the infectious Middle East Respiratory Syndrome (MERS) virus, have multiple enzymatic activities that promote viral infection. PLpro acts as a protease and processes the large coronavirus polyprotein for virus replication. PLpro also functions as both a deubiquitinating (DUB) and deISGylating (deISG) enzyme and removes ubiquitin (Ub) and interferon-stimulated gene 15 (ISG15) from cellular proteins. Both D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 33 publications
3
52
0
1
Order By: Relevance
“…K232E, Fig EV3F). Similar experiments have recently been described for MERS PLpro (Clasman et al , ).…”
Section: Resultssupporting
confidence: 74%
“…K232E, Fig EV3F). Similar experiments have recently been described for MERS PLpro (Clasman et al , ).…”
Section: Resultssupporting
confidence: 74%
“…In agreement with another work [58], it was shown that while SARS-CoV-2 PL pro retained de-ISGylating activity similar to its SARS-CoV counterpart, its hydrolyzing ability of diUb K48 was decreased [59]; this might not be surprising, since specificity for Ub and ISG15 substrates might depend on only one mutation [60][61][62], and while the Ub S1 site is conserved between the PL pro s of SARS-CoV and SARS-CoV-2 (83% similarity, 17% identity), the Ub S2 site has only 67% similarity and 13% identity. Interestingly, SARS-CoV-2 PL pro displays preference for ISG15s from certain species including humans [58].…”
Section: Introductionsupporting
confidence: 89%
“…The overall assembly of SCoV2-PLpro and both ISG15 domains was similar to the MERS-PLpro-humanISG15 complex (PDB ID: 6BI8, Extended data Fig. 2a) 15 . The catalytic cysteine residue is also conserved in SARS (Extended data Fig.…”
Section: Scov2-plpro-isg15 Structural Analysismentioning
confidence: 69%